Seleksi Progeni F1 Sebagai Klon Unggul Penghasil Lateks dan Lateks Kayu - Amorrito Surbakti; Rosmayati Rosmayati; Luthfi A. M. Siregar (Universitas Sumatera Utara, 2015)
The objective of this research was to get the best progeny based on potential of latex yield characteristic, timber yield characteristic and latex-timber yield resulted from 2008 hand pollination. The research was conducted in ± 54 m above sea level at Balai Penelitian Sungei Putih Pusat Penelitian Karet Galang Deli Serdang Sumatera Utara Medan from February 2014 - July 2014. The research was done by measuring coefisien varians, correlation, regression, path analysis, 10 % and 1 % selection intensity, and two line pattern.The research showed based on selection latex yield are 172/08 (intensity 10% and 1%), based on selection timber yield with intensity 10 % and 1 % are 172/08 and 173/08. Progeny 172/08 potential as latex and timber yielding for 2008 hand pollination.Keywords :Hevea brasiliensis, progeny,path analysis, selection